Parametric effects and optimization on synthesis of iron (II) doped carbonaceous catalyst for the production of biodiesel. (15th August 2016) - Dhawane, Sumit H.; Kumar, Tarkeshwar; Halder, Gopinath
Highlights: Iron (II) was doped on activated carbon surface. L9 orthogonal array was used for experimental design using Taguchi approach. Parametric effects of catalyst synthesis on biodiesel yield were studied. Agitation speed was emerged as most influential parameter. Cost analysis of catalyst shows it is cost effective and eco-friendly. Abstract: Synthesis of efficient and low cost heterogeneous catalyst for transesterification of triglycerides into esters is the need of the hour. The present study elaborates an indigenous development of ferromagnetic iron (II) doped carbonaceous catalyst (Fe/C) for the production of biodiesel from rubber seed oil. The parametric effects on the synthesis of Fe/C catalyst were studied to identify the most significant parameters affecting the biodiesel yield using Taguchi method. The doping process was optimised for maximum biodiesel yield considering four parameters viz. Impregnation time, temperature, catalyst content and agitation speed. The prepared catalyst was characterized using scanning electron microscopy (SEM), X-ray energy dispersive analysis (EDX), X-ray diffraction (XRD), thermo gravimetric analysis (TGA) and Fourier transform infrared spectrometer (FT-IR). The contribution factor revealed that agitation speed is the most influential parameter affecting the biodiesel yield followed by catalyst content, impregnation time and temperature. The maximum biodiesel yield observed in optimum condition of impregnation time 15 h, impregnation temperature 40 °C, catalyst content 5 wt% and agitation speed 500 rpm was 96.31%. The cost analysis of catalyst synthesis was done and found to be fairly economical. The reusability of the catalyst was tested to check the decay in catalytic activity at the optimised condition and found to decrease in activity by 0.8–1.2% after three cycles. Thus, the experimental results and characterization study confirm that indigenously developed carbonaceous catalyst from waste material doped with iron (II) is cost effective and capable of transesterifying the rubber seed oil into rubber seed methyl ester (RSME) with appreciable catalytic activity in reusability.